Longitudinal serological and virological survey of hepatitis E virus in wild boar (Sus scrofa majori, Maremman wild boar) and fallow deer (Dama dama) populations in a protected area of Central Italy - De Sabato, Luca; Domanico, Mariagiovanna; De Santis, Paola; Cecca, Daniele; Bonella, Giulia; Mastrandrea, Giovanni; Onorati, Roberta; Sorbara, Luigi; Varcasia, Bianca Maria; Franzetti, Barbara; Caprioli, Andrea; Battisti, Antonio; et al. (Frontiers in Veterinary Science, 2024)
Hepatitis E virus (HEV) is recognized as an emerging zoonosis. Pigs and wild boars are considered the main reservoirs of zoonotic HEV-3 and HEV-4 genotypes. In Europe, autochthonous human cases of hepatitis E, mainly associated with HEV-3 and consumption of raw or undercooked pig and wild boar liver/meat, have increased over the last decades. From 2016 to 2024, during several hunting seasons, we conducted a molecular and serological longitudinal survey on the circulation of HEV in Maremman wild boar (Italian subspecies/ecotype, Sus scrofa majori) and fallow deer (Dama dama) populations in a protected area in Central Italy. During the study period, 346 livers (256 from wild boar, 90 from fallow deer), 161 serum (127 from wild boar, 34 from fallow deer), and 23 meat juice (11 from wild boar, 12 from fallow deer) samples were collected. Serum and meat juice samples were tested using a commercial ELISA test for the detection of total anti-HEV antibodies. An estimated serological prevalence of 28.3% (39/138) in wild boar and 21.7% (10/46) in fallow deer was found. The 346 liver samples were tested using a HEV Real-Time RT-PCR for the detection of HEV-RNA. Thirty-one wild boar (12%) and four fallow deer (4.4%) livers were found positive. Phylogenetic analysis of 11 partial ORF2 sequences from wild boar confirmed the HEV3 heterogeneity in this species, revealing different strains (3f, 3c) circulating over the years. The detected subtypes are among the most commonly detected in Italy and our strains showed a high correlation with human and wild boar Italian strains. Although the studied area is a fenced natural reserve, the presence of different strains over time suggests the probable virus introduction from the external. Our results confirm fallow deer susceptibility to the infection, and that wild boar could be considered the main wild HEV reservoir. This is also the first study demonstrating the infection in the so-called Italian subspecies/ecotype Maremman wild boar. Moreover, our results corroborate that the consumption of undercooked or raw liver from both wild boar and fallow deer, or the direct contact with these animals, could represent a zoonotic risk.